Echo tail canceller based on AIFIR filtering. - Abousaada, Anis Ahmed. (University of Ottawa (Canada), 1990)
This thesis contributes a computationally efficient echo tail canceller. The proposed structure is an adaptive version of the Interpolated FIR (IFIR) filter. The results obtained with this new approach are compared to those obtained with an AFIR direct form echo canceller. The proposed system requires approximately 31% of the hardware of the AFIR echo canceller. A two-stage echo canceller utilized in the U-interface at Basic Rate Access-ISDN is investigated. The first stage (Main Echo Canceller) is comprised of an AFIR filter which cancels the main echo pulse amid the first few symbol intervals. Cancellation of the echo tail is performed by the AIFIR tail canceller. To evaluate the performance of this architecture, echo impulse responses were produced for the Bellcore loop structures. These investigations were on the effects of parameters such as the passband edge and the stopband attenuation of the interpolator as well as length of the first stage echo canceller. (Abstract shortened by UMI.)
Keywords: Engineering, Electronics and Electrical.